Cognitive Rehabilitation of Adaptive Behavior in Children with Neurodevelopmental Disorders: A Meta-Analysis - Si-nae Ahn; Sujin Hwang (Hindawi-Wiley, 2018)
Objectives. Negative behavioral problems often occur following the onset of neurodevelopmental disorders and have an overall impact on the affected children, specifically in terms of their social developmental level. In children, social development behavior has been shown to spontaneously mature over time with the cognitive therapy intervention effects. This study performed a meta-analysis to provide a statistical synopsis of the available evidence of social development behavioral changes following cognitive therapy in children with neurodevelopmental disorders. Methods. Data was collected from two online search engines, including EBSCOhost and PubMed, from January 1, 2006, to August 31, 2016, using the terms "cognition," "cognitive function," and "disease including neurodevelopmental disorder with DSM-5." Two assessors searched the literature using independent inclusion criteria and evaluated the quality of results using the Jadad score. Six articles were chosen using the Comprehensive Meta-Analysis program (version 2.0). Results. Six articles reporting randomized controlled trial studies were included. The effective scores for improving adaptive behavior following cognitive therapy in children with neurodevelopmental disorder were 0.64. The effective score of adaptive behavior was significant in this study (p<0.05). The results showed no significant statistical heterogeneity and publication bias. Conclusions. The findings of the meta-analysis suggest that cognitive interventions are effective at improving adaptive behavior associated with neurodevelopmental disorders.